Knowledge of Lobbying Regulations and Attitudes Toward Politics: Findings from a Survey Experiment in Cyprus. (4th March 2018) - Kanol, Direnç
Abstract : Does knowledge of lobbying regulations curb perceptions of political corruption and increase trust in politicians? The survey experimental data presented in this article suggest that a rise in trust in politicians through knowledge of lobbying regulations is harder to achieve than a decline in perceptions of political corruption. In the case of trust in politicians, only full disclosure makes a substantive difference. In the case of perceived political corruption, some disclosure is enough to affect perceptions significantly, although full disclosure is necessary to make a substantive difference. These results suggest that policymakers should take lobbying reform seriously and consider enacting and disseminating stringent lobbying regulations.